You are on page 1of 74

# POLITEHNICA University of Bucharest Faculty of Aerospace Engineering

Constant Coeff

variable Coeff

Homog(find yp)

NON-HOMOG
(find yp)

Cauchy-Euler

## In General Power Series

Variational of Parameters

Diff_Eq_8_2012

Sec 6.1: Solution about Ordinary Points Sec 6.1.1: Review of Power Series Sec 6.1.2: Power Series Solutions Sec 6.2: Solution about Singular Points

Diff_Eq_8_2012

## Power Series Definition Power Series Function by series Representing

An expression of the form

## is a power series centered at x = 0. An expression of the form

n =0

n 2 n L c x = c + c x + c x + + c x +L n o 1 2 n

cn ( x a ) n
=0

=c o + c 1 ( x a ) + c 2 ( x a ) + L + c n ( x a ) + L
2

is a power series centered at x = a . The term c n ( x a ) is the nth terms; the number of a is the center.
Diff_Eq_8_2012

## Power Series Radius of convergence

Theorem 5 The Convergence Theorem for Power Series There are three possibilities for an ( x a ) with respect to
n n =0

convergence: 1. There is a positive number R such that the series diverges for

x a > R but converges for x a < R. The series may or may not converges at either of the endpoints x = a R and x = a + R. 2. The series converges for every x (R = ). 3. The series converges at x=a and diverges elsewhere (R = 0).

The positive number R in the previous theorem is called the radius of convergence for the given power series. Diff_Eq_8_2012

## Power Series Radius of convergence

Given a power series in its general form a0 + a1(x - c) + a2(x - c)2 + a3(x - c)3 + the radius of convergence is
an 1 R = lim | |= lim n a n n a n +1 n

## provided that it exists or is equal to .

Diff_Eq_8_2012

Radius of Convergence = R

a ( x a)
n =0 n

Converges for

x a < R

aR

a+R

a ( x a)
n =0 n

Converges absolutely

if

a ( x a)
n =0 n

Converges

Diff_Eq_8_2012

## Sum and Difference of power series

Suppose that we have two functions defined by power series f(x) = a0 + a1(x - c) + a2(x - c)2 + a3(x - c)3 + with radius of convergence R1 and g(x) = b0 + b1(x - c) + b2(x - c)2 + b3(x - c)3 + with radius of convergence R2 , then
f ( x) g ( x) = (an bn )( x c) n
n =1

Power Series

Diff_Eq_8_2012

Power Series

## Product of power series

Suppose that we have two functions defined by power series f(x) = a0 + a1(x - c) + a2(x - c)2 + a3(x - c)3 + with radius of convergence R1 and g(x) = b0 + b1(x - c) + b2(x - c)2 + b3(x - c)3 + with radius of convergence R2 , then f(x)g(x) = a0 b0 + [a1 b0 + a0 b1 ](x - c) + [a2 b0 + a1 b1 + a0 b2](x - c)2 + [a3 b0 + a2 b1 + a1b2 + a0 b3](x - c)3 + and the radius of convergence is min{R1 , R2} unless either f(x) = 0 or g(x) = 0.
Diff_Eq_8_2012

Product of Power Series Power series can be combined through the operations of addition, multiplication and division.
e x sin x x 2 x3 x 4 x3 x5 x7 = x 6 + 120 5040 L 1 + x + 2 + 6 + 24 + L 1 1 3 1 1 4 1 1 1 5 2 + x + L = (1) x + (1) x + + x + + x + 120 12 24 6 6 6 2
3 5 x x = x + x2 + L 3 30
Diff_Eq_8_2012

Power Series

## Differentiation and Integration

Theorem Term - by term Differentiation
If f ( x ) = c n ( x a ) = c o + c 1 ( x a ) + c 2 ( x a ) + L + c n ( x a ) + L
n 2

## converges for | x a |< R , then the series

n =0

nc n ( x a )
n =1

n 1

= c 1 + 2c 2 ( x a ) + 3c 3 ( x a ) + L + nc n ( x a )
2

n 1

+L

obtained by differentiating the series for f term by term, converges for | x a |< R , and represents f (x ) on that interval. If the series for f converges for all x , then so does the series for f .
Diff_Eq_8_2012

## Power Series Differentiation and Integration

Theorem 2 Term - by - Term Integration
If f ( x ) = c n ( x a ) = c o + c 1 ( x a ) + c 2 ( x a ) + L + c n ( x a ) + L
n 2

## converges for | x - a |< R , then the series

cn n
=1

n =0

( x a )n +1
n +1

= co ( x a ) + c1

( x a )2
2

+ c2

( x a )3
3

+ L + cn

( x a )n +1
n +1

+L

obtained by integrating the series for f term by term, x converges for | x - a |< R , and represents a f (t )dt on that interval. If the series for f converges for all x , then so does the series for the integral.

Diff_Eq_8_2012

## Power Series Taylor Series of a Function

Suppose that a given function f(x) does have a power series representation f(x) = a0 + a1(x - a) + a2(x - a)2 + a3(x - a)3 + and we would like to find its coefficients an. We further have to assume that f(x) is infinitely differentiable at the point a, then its not hard to see that f(a) = a0 , f (a) = a1 , f (a) = 2a2 , f (3)(a) = 6a3 , f (n)(a) = n!an
a0 = f (a) a1 = f '(a)

thus

a2 =

f ''(a) 2!
n

Diff_Eq_8_2012

f ( ) (a) an = n!

## Power Series Taylor Series of a Function

Theorem Taylor's Theorem with Remainder IF f : I R ,f C (I) [i.e. has derivatives of all orders in a open interval I containing a ], then for each positive integer n and for each x in I ,
f (n ) (a ) f ( x ) = f (a ) + f (a ) ( x a ) + (x a ) +L+ ( x a )n + n! 2! + Rn ( x )
2

f (a )

where

## for some c between a and x .

Diff_Eq_8_2012

f (n +1) (c ) Rn ( x ) = ( x a )n +1 (n + 1)!

## Power Series Maclaurin Series of a Function

Definition: Suppose that f(x) is infinitely differentiable in a neighborhood of a point a, then the Maclaurin Series of f is the Taylor series of f at a = 0, i.e.
f ( x ) = f ( a ) + f '( a )( x a ) + f ''( a ) f '''( a ) ( x a)2 + ( x a )3 + 2! 3! L

a=0

Diff_Eq_8_2012

## Power Series Maclaurin and Taylor Series

2n x 1 1 1 1 cos(x ) = 1 2! x + 4! x 6! x + 8! x K = (-1) (all real x ) (2n )! n =0 2n +1 x 3 5 7 9 n 1 1 1 1 sin(x ) = x 3! x + 5! x 7! x + 9! x K = (-1) (all real x ) (2n + 1)! n =0 2 4 6 8

## Taylor series (Maclaurin series) for several functions

n

1 1 1 e = 1 + x + 2! x + 3! x + 4! x +K =

1 n x n =0 n !

(all real x )

## Operations of Power series: Theorems

(1) Equality of power series If
n n a ( x x ) = b ( x x ) , with n n a a n =0 n =0

R0

then Corollary

an = bn

,for all n

## n a ( x x ) = 0, all an=0, for all n ,R>0 If n a n=0

Diff_Eq_8_2012

Identity Property If
n c ( x a ) =0 n n =0

cn = 0
analytic at

f (x )

Is

x0 x
0

## f ( x ) Can be represented by power series centerd at

f (x ) = c n (x x 0 )n
n =0

with

R>0

x x0 < R

Example :

## Any polynomial such as

f 1 (x ) = e x
f 2 ( x ) = sin x f 3 ( x ) = cos x
Diff_Eq_8_2012

3 + 2x 4x 2 + 6x 3 x x2 x3 f 1 (x ) = 1 + + + + KK 1! 2! 3!

x3 x5 f 2 (x ) = x + KK 3! 5!
x2 x4 f 3 (x ) = 1 + KK 2! 4!

R =

Example:

n (n 1)c n x
n =0

n +2

+ nc n x n + 2
n =2

Example:

## write as a single power series

n 2 n +1 n ( n 1) c x + c x n n n =2 n =0

Diff_Eq_8_2012

Power Series for solving Ordinary Differential equations with non-constant coefficients

Diff_Eq_8_2012

## Power Series Solution

Suppose the linear DE a2 ( x) y + a1 ( x) y + a0 ( x) y = 0 is put into y + P( x) y + Q( x) y = 0
DEFINITION

A point x0 is said to be an ordinary point if both P and Q are analytic at x0. A point that is not an ordinary point is said to be a singular point.
Since P and Q in is a rational function, P = a1(x)/a2(x), Q = a0(x)/a2(x) It follows that x = x0 is an ordinary point if a2(x0) 0.
Diff_Eq_8_2012

Singular Points
Definition: IF: (i.e)

f (x )

Is

analytic

at

x0 x
0

## f ( x ) Can be represented by power series centerd at

f (x ) = c n (x x 0 )n
n =0

with

R>0

x x0 < R

Definition:

x0

Is

## an ordinary point of the DE (*)

y ''+ P ( x ) y '+ Q ( x ) y = 0
IF:

(*)
x
0

P ( x ) and Q ( x )

are analytic at

A point that is not an ordinary point of the DE(*) is said to be singular point Special Case: Polynomial Coefficients

Example :
1) 2) ( x 2 25) y ''+ 2xy '+ y = 0 (x 2 -4) 2 y ''+ 3(x 2) y '+ 5 y = 0

a2 ( x ) y ''+ a1 ( x ) y '+ a0 ( x ) y = 0
a2 ( x0 ) = 0 x0 singular point ordinary point a2 ( x0 ) 0 x0 Diff_Eq_8_2012

3)

Definition:

x0

Is

## a regular singular point of the DE (*)

y ''+ P ( x ) y '+ Q ( x ) y = 0
IF:

(*)
x
0

p ( x ) and q ( x )

are analytic at

where p ( x ) = ( x x 0 ) P ( x ) and q ( x ) = ( x x 0 ) 2Q ( x )
A singular point that is not a regular singular point of the DE(*) is said to be irregular singular point

Example :

2)

(x 2 - 4) 2 y ''+ 3( x 2) y '+ 5 y = 0

3)
Diff_Eq_8_2012

xy '' 2 xy '+ 8 y = 0

Theorem :

## Existence of Power Series Solutions

a2 ( x ) y ''+ a1 ( x ) y '+ a0 ( x ) y = 0
IF x 0 is an ordinary point

n c ( x x ) n 0

with

x x0 < R

Diff_Eq_8_2012

## Power series method (Contd)

Solution is expressed in the form of a power series.

Let

y = am x m = a0 + a1 x + a2 x 2 + a3 x3 + ..........
m=0

so,

m =1

m=2
Diff_Eq_8_2012

## Power series method (Contd)

Substitute

y, y , y

'

''

Collect like powers of x Equate the sum of the co-efficients of each occurring power of x to zero. Hence the unknown co-efficients can be determined.

Diff_Eq_8_2012

Example 1
Solve

d2y + y=0 2 dx
y = cn x n = c0 + c1 x + c2 x 2 + c3 x 3 + ....

P( x) = 0, Q( x) = 1, R( x) = 0
dy 2 = c1 + 2c2 x + 3c3 x + .... = ncn x n 1 dx n =1

Consider x0=0

n =0

## d2y = 2c2 + 3 2c3 x + .... = n(n 1)cn x n 2 2 dx n=2

n=2

n(n 1)cn x

n2

+ cn x n = 0
n =0

replacing n by n+2

Diff_Eq_8_2012

n =0

n n ( n + 2 )( n + 1 ) c x + c x n =0 n+2 n =0

Example 1
n =0 n [ ] ( n + 2 )( n + 1 ) c + c x =0 n+2 n

## The coefficient of each power of x must be zero; that is,

(n + 2)(n + 1)cn+ 2 + cn = 0
c0 c = 0 2 2! c c c3 = 1 = 1 6 3! c c c4 = 2 = 0 12 4! c c c5 = 3 = 1 20 5! c2 =

n = 0; n = 1; n = 2; n = 3;

2c2 + c0 = 0, 3 c3 + c1 = 0,

thus thus

(1) k c2 k = c0 (2k )!

k = 1, 2,...

## (1) k c2 k +1 = c1 k = 0,1, 2,... (2k + 1)!

x2 x4 (1) n 2 n x3 x5 (1) n 2 n 1 + ... y = c0 1 + + ... + x + ... + c1 x + + ... + x (2n)! 3! 5! (2n + 1)! 2! 4! = c0 cos x + c1 sin x
Diff_Eq_8_2012

Example 2
( x + 1) y + xy y = 0
2

y ( x ) = cn x n (analytic at x = 0)
n =0

## Radius of convergence? Step 1

(x
n=2

+ 1) n ( n 1) cn x
n=2 n n=2

n2

+ x ncn x
n =1 n2

n 1

cn x n = 0
n =0 n n =0

n ( n 1) cn x + n ( n 1) cn x
Step 2
k =2

+ ncn x cn x n = 0
n =1

k=n
k

k=n2
k

k=n
k

k=n

k k k 1 c x + k + 2 k + 1 c x + kc x c x ( ) ( )( ) k k =0 k k +2 k =0 k =1 k =0

Diff_Eq_8_2012

k k k 1 c x + k + 2 k + 1 c x + kc x c x ( ) ( )( ) k k =0 k k +2 k k k k =2 k =0 k =1 k =0

## Step 3 2c2 c0 + (6c3 + c1 c1 ) x k=0 k=1

+ [k ( k 1) ck + ( k + 2 )( k + 1) ck + 2 + kck ck ]x k = 0
k =2

## 2c2 c0 + 6c3 x + [(k +1) ( k 1) ck + ( k + 2 )( k + 1) ck + 2 ]x k = 0

k =2

Step 4

2c2 c0 =0

6c3 =0

ck +2 = k 1 ck k+2

Diff_Eq_8_2012

2c2 c0 =0 c2 =c0 /2
c0, c1

6c3 =0 c3 =0

ck + 2 = 1 k ck k +2

c2 =c0 /2 c3 =0
c4 = 1 c2 = 1 c0 = 21 c0 4 24 2 2! c5 = 2 c3 = 0 5 c6 = 3 c4 = 3 c0 = 33 c0 6 246 2 3!

c7 = 4 c5 = 0 7 5 c c8 = 5 c6 = 3 5 c0 = 3 4 8 2 4 6 8 2 4! 0 c9 = 6 c7 = 0 9 : :

Diff_Eq_8_2012

Step 5
2 4 6 8 10 x x 3 x 3 5 x 3 5 7 x LL + c1 x y ( x ) = cn x = c0 1 + 2 + 3 4 + 5 2 2 2! 2 3! 2 4! 2 5! n =0 y2 y 1 y ( x) = c y ( x) + c y ( x) n 0 1 1 2

y2 ( x ) = x

## |x| < 1 (Why?)

Diff_Eq_8_2012

Example 2
Solve y"+ (cos x) y = 0 Solution We see x = 0 is an ordinary point of the equation. Using the Maclaurin series for cos x, and using y = c n x n n=0 y + (cos x ) y , we find

= n ( n 1)cn x n 2
n=2

x2 x4 x6 n + + + L c x 1 n 2 ! 4 ! 6 ! n =0

## 1 2 1 3 = 2c2 + c0 + (6c3 + c1)x + 12c4 + c2 c0 x + 20c5 + c3 c1 x + L 2 2 =0

Diff_Eq_8_2012

Example 2
It follows that

and so on. This gives c2 =1/2c0, c3 =1/6c1, c4 = 1/12c0, c5 = 1/30c1,. By grouping terms we get the general solution y = c0y1 + c1y2, where the convergence is |x| < , and

## 1 1 2c2 + c0 = 0 , 6c3 + c1 = 0 , 12c4 + c2 c0 = 0 , 20c5 + c3 c1 = 0 2 2

1 2 1 4 y1 ( x) = 1 x + x L 2 12 1 3 1 5 y2 ( x ) = 1 x + x L 6 30
Diff_Eq_8_2012

Examples

Example 1: Solve

y y=0
'

Example 2: Solve

y = 2 xy
'

Example 3: Solve

y +y=0
''

Diff_Eq_8_2012

Frobenius Theorem
Theorem : IF x 0 is a regular singular point

a2 ( x ) y ''+ a1 ( x ) y '+ a0 ( x ) y = 0
1) There exists at least one solution in the form y = ( x x0 )
r

c (x x ) = c (x x )
n n =0 n 0 n 0

n+r

Remember!!

x0

Is

## a regular singular point of the DE (*)

y ''+ P ( x ) y '+ Q ( x ) y = 0
IF:

(*)
x
0

p ( x ) and q ( x )

are analytic at

where p ( x ) = ( x x 0 ) P ( x ) and q ( x ) = ( x x 0 ) 2Q ( x )
Diff_Eq_8_2012

Frobenius Theorem
Theorem : IF x 0 is a regular singular point

a2 ( x ) y ''+ a1 ( x ) y '+ a0 ( x ) y = 0
1) There exists at least one solution in the form

(x x 0 ) n + r

## 2) The series will converge at least on some interval 0 < x - x0 < R

Example :

(x 2 - 4) 2 y ''+ 3( x 2) y '+ 5 y = 0
n +r c ( x 2) n n =0

X=2 is a regular singular point . We can find at least one sol in the form

with
Diff_Eq_8_2012

0< x 2< R

Frobenius Theorem
Theorem : IF x 0 is a regular singular point

a2 ( x ) y ''+ a1 ( x ) y '+ a0 ( x ) y = 0
1) There exists at least one solution in the form

(x x 0 ) n + r

2) The series will convereg at least on some interval 0 < x -x0 < R

Example :

## xy '' 2xy '+ 8 y = 0

n +r c x n n =0

X=0 is a regular singular point . We can find at least one sol in the form

with
Diff_Eq_8_2012

0<x <R

## We need to find all Cn and r

Indicial Equation
2nd order case y + P ( x ) y + Q ( x ) y = 0 If x0 is a regular singular point

( x x0 ) 2 y + ( x x0 ) p ( x ) y + q ( x ) y = 0
where p ( x ) = ( x x0 ) P ( x ) p(x) and q(x) are analytic

q ( x ) = ( x x0 ) 2 Q ( x )
2

p ( x ) = a0 + a1 ( x x0 ) + a2 ( x x0 ) + LLL
q ( x ) = b0 + b1 ( x x0 ) + b2 ( x x0 ) + LLL
2

y ( x ) = cn ( x x0 )
n =0

n+ r

y ( x ) = cn (n + r ) ( x x0 )
n =0

n + r 1

,
n+ r 2

y ( x ) = cn (n + r )(n + r 1) ( x x0 )
Diff_Eq_8_2012
n =0

## y(x), y'(x), y''(x), p(x), q(x) ( x x0 ) 2 y + ( x x0 ) p ( x ) y + q ( x ) y = 0

cn (n + r )(n + r 1) ( x x0 )
n =0

n+r

+ a0 + a1 ( x x0 ) + a2 ( x x0 ) + LLL
2

( (

cn (n + r ) ( x x0 )
n =0 n+r

n+ r

+ b0 + b1 ( x x0 ) + b2 ( x x0 ) + LLL
2

cn ( x x0 )
n =0

=0

## (x x0) r is the smallest coefficient equal to 0.

c0 r (r 1) + c0 a0 r + c0b0 = 0 r (r 1) + a0 r + b0 = 0
indicial equation

Diff_Eq_8_2012

## For the 2nd order case

r (r 1) + a0 r + b0 = 0

## (Case 1) r1 r2 and r1, r2 are real, r2 r1 positive integer

y1 ( x) = cn ( x x0 )
n =0

n + r1

and y2 ( x) = bn ( x x0 )
n =0

n + r2

## (Case 2) r1 r2 and r1, r2 are real, r2 r1 = integer

y1 ( x) = cn ( x x0 )
n =0

n + r1

, c0 0
n + r2

y2 ( x) = Cy1 ( x)ln x + bn ( x x0 )
n =0
Diff_Eq_8_2012

, b0 0

## where C is a constant that could be zero.

(Case 3) r1 = r2

y1 ( x ) = cn ( x x0 )
n =0

n + r1

, c0 0
n + r2

y2 ( x ) = y1 ( x ) ln x + bn ( x x0 )
n =1

## (Case 4) r1 r2 and r1, r2 are complex

If we already have a known solution y1, then the second solution can be obtained by the method of reducton of order.

y2 ( x) = y1 ( x)
Diff_Eq_8_2012

## exp( P( x)dx) y12 ( x)

dx

Provenext page.

Prove

F ro m y + P ( x ) y + Q ( x ) y = 0, w e g et y1 + P ( x ) y1 + Q ( x ) y 1 = 0 y 2 y1 + P ( x ) y1 + Q ( x ) y1 = 0 (1) y 2 + P ( x ) y 2 + Q ( x ) y 2 = 0 y1 y 2 + P ( x ) y 2 + Q ( x ) y 2 = 0 ( 2 ) B y ( 2 ) - (1), y1 y 2 y 2 y1 + P ( x ) y1 y 2 y 2 y1 = 0

( y1 y 2 y 2 y1 ) + P ( x ) y1 y 2 y 2 y1 = 0 y1 y 2 y 2 y1 = c ex p ( P ( x ) d x ) c ex p ( P ( x ) d x ) y1 y 2 y 2 y1 = 2 y1 y 12 c ex p ( P ( x ) d x ) y2 d( ) = y1 y12 y2 = y1

c ex p ( P ( x ) d x ) y
2 1

, let c = 1, .

Diff_Eq_8_2012

so y 2 = y 1

ex p ( P ( x ) d x ) y
2 1

Frobenius Theorem
Example :

Solve:

xy ''+ y = 0
n +r c x n n =0

X=0 is a regular singular point . We can find at least one sol in the form

## We need to find all Cn and r

y = c 0x

+ c 1x

1+ r

+ c 2x

2+r

+ c 3x

3+ r

+ c 4x

4+r

+KK

y ' = rc 0 x r 1 + (1 + r )c1x r + (2 + r )c 2 x 1+ r + (3 + r )c 3 x 2+ r + (r + 4)c 4 x 3+ r + KK y '' = r ( r 1)c 0 x r 2 + (1 + r ) rc1x r 1 + (2 + r )(1 + r )c 2 x r + +(3 + r )(2 + r )c 3 x 1+ r + ( r + 4)(3 + r )c 4 x 2 + r + KK xy '' = r ( r 1)c 0 x r 1 + (1 + r ) rc1x r + (2 + r )(1 + r )c 2 x r +1 + +(3 + r )(2 + r )c 3 x 2 + r + ( r + 4)(3 + r )c 4 x 3+ r + KK
Diff_Eq_8_2012

## Indicial Equations ( indicial roots)

indicial equation is a quadratic equation in r that results from equating the total coefficient of the lowest power of x to zero
Example :

xy ''+ y = 0

r ( r 1) = 0 r1 = 1 > r2 = 0
(*)

## indicial equation indicial roots

y ''+ P ( x ) y '+ Q ( x ) y = 0

## where p ( x ) = xP ( x ) and q ( x ) = x 2Q ( x ) a 0 =p (0) and b 0 =q (0)

indicial equation
Diff_Eq_8_2012

r ( r 1) + a0 r + b 0 = 0

## Indicial Equations ( indicial roots)

y ''+ P ( x ) y '+ Q ( x ) y = 0 (*)

indicial equation

## where p ( x ) = xP ( x ) and q ( x ) = x 2Q ( x ) a 0 =p (0) and b 0 =q (0)

r ( r 1) + a0 r + b 0 = 0

Example :

## Find the indicial roots:

indicial equation

Example :

r (3r 2) = 0

## Find the indicial roots:

indicial equation

## 2xy ''+ (1 + x ) y '+ y = 0

Diff_Eq_8_2012

r (2r 1) = 0

Example ( x 2 4) 2 y + 3( x 2) y + 5 y = 0

P ( x) =

3 ( x 2)( x + 2) 2

Q ( x) =

5 ( x 2) 2 ( x + 2) 2

x = 2 is a x = 2 is a

? ?

point point

Diff_Eq_8_2012

Example 2

3 xy + y y = 0
Step 1

y ( x ) = cn x n+ r
n =0
n =0 n =0

3 cn (n + r )(n + r 1) x n+ r 1 + cn (n + r ) x n+ r 1 cn x n+r = 0
n =0

Step 2 Power

k=n

k=n

n=k1 k=n+1

3 ck (k + r )(k + r 1) x k + r 1 + ck (k + r ) x k + r 1 ck 1 x k + r 1 = 0
k =0 k =0 k =1
Diff_Eq_8_2012

Step 3

[3c0r (r 1) + c0r ] x
Step 4

r 1

+ [3ck (k + r )(k + r 1) + ck (k + r ) ck 1 ] x k +r 1 = 0
k =1

3r (r 1) + r = 0
Step 5

3r 2 2r = 0

r (3r 2) = 0

r = 0 or 2 / 3 3ck (k + r )(k + r 1) + ck (k + r ) ck 1 = 0
ck = 1 ck 1 (k + r )(3k + 3r 2)

Diff_Eq_8_2012

ck =
Step 6

1 ck 1 (k + r )(3k + 3r 2)
r = 2/3

r=0

ck 1 ck = k (3k 2)

ck =

1 c (3k + 2)k k 1

:

## c0 5 1 c c c2 = 1 = 0 8 2 2!5 8 c1 = c0 c2 c3 = = 11 3 3!5 8 11 c c0 c4 = 3 = 14 4 4!5 8 1114 : c0 cn = n!5 8 11LL(3n + 2)

c0 cn = n!1 4 7LL(3n 2)
Diff_Eq_8_2012

Solution of Example 2

y = C1 y1 + C2 y2
1 y1 ( x ) = x 1 + xn n=1 n!1 4 7LL(3n 2) 0

y2 ( x ) = x

2/3

## n 1 1 + n!5 8 11LL(3n + 2) x n=1

x ( 0, )

Diff_Eq_8_2012

Examples 4, 5

xy + y = 0
Step 1

y ( x ) = cn x n+r
n =0

cn (n + r )(n + r 1) x
n =0

n + r 1

+ cn x n+r = 0
n =0

Step 2
k =0

n=k

n = k 1
k + r 1

ck (k + r )(k + r 1) x
Step 3
k =1

+ ck 1 x k + r 1 = 0
k =1

c0 r (r 1) x r 1 + [ck (k + r )(k + r 1) + ck 1 ]x k + r 1 = 0

Diff_Eq_8_2012

## Step 4 Step 5 Step 6

r (r 1) = 0 r = 0 or 1 ck 1 ck = (k + r )(k + r 1)
r=1

ck =

ck 1 (k + 1)k

cn = (1) n

c0 (n + 1)!n !

## (1)n n (1)n n y1 ( x ) = x 1 + x = x x + + n n n n !( 1)! !( 1)! n=1 n =0 (1)n n+1 = x n n + !( 1) ! n =0

Diff_Eq_8_2012

Step 6

r=0

ck 1 ck = (k 1)k

k=1
Step 3

ck (k + r )(k + r 1) + ck 1 = c1 0 + c0 = 0
(k = 1, r = 0 )

c0=0, real c1

c1 c2 = 1 2 c1 cn = (n 1)! n!
0

c2 c1 c3 = = 2 3 1 2 2 3

(1)n1 n (1)n1 n (1)m y2 ( x ) = x x + x = x = x m+1 m!(m + 1)! n=2 (n 1)!n! n=1 (n 1)!n! m =0 m=n1

Diff_Eq_8_2012

Special Functions
Bessels equation of order v

x 2 y + xy + ( x 2 v 2 ) y = 0

Solution: c1 J v ( x ) + c2Yv ( x )
2 n+v

(1) n x Jv ( x) = n! (1 + v + n ) 2 n =0

()

## cos v J v ( x ) J v ( x ) Yv ( x ) = sin v Legendres equation of order n

(1 x 2 ) y 2 xy + n(n + 1) y = 0

## One of the solution: Legendre polynomials

Diff_Eq_8_2012

57

Gamma function

( x ) = t x1e t dt
0

modified Bessel equation of order v c1Iv( x) + c2Kv(x) x 2 y + xy ( x 2 + v 2 ) y = 0 modified Bessel equation of the 1st kind modified Bessel equation of the 2nd kind

## modified Bessel equation of the 3nd kind x 2 y + (1 2a ) xy + (b 2c 2 x 2 c + a 2 p 2c 2 ) y = 0

I v ( x ) = i v J v ( ix ) I v ( x ) I v ( x ) Kv ( x ) = sin v 2

c c y = xa c J ( bx ) c Y ( bx ) + 2 p 1 p

## spherical Bessel functions

v = 1 , 3 , 5 , LL 2 2 2

Diff_Eq_8_2012

## 6.3.1 Bessels Equation

6.3.1.1 Solving for Bessels equation of order v

x 2 y + xy + ( x 2 v 2 ) y = 0
Steps 1~3

y ( x ) = cn x n+r
n =0

c0 (r v ) x + c1 ((1 + r ) v ) x
2 2
r

r +1

+ [ck ((k + r ) 2 v 2 ) + ck 2 ]x r +k = 0
k =2

Step 4 r 2 v 2 = 0

## two roots: v and v

ck = ck 2 v 2 (k + r )2

2 2 Step 5 c1 ( (1 + r ) v ) = 0

c1 = 0
Diff_Eq_8_2012

ck =

ck 2 v 2 (k + r )2

59

Step 6 r = v

ck =

ck 2 k ( k + 2v )

r = v

ck =

ck 2 k ( k 2v )

c1 = 0, c3 = c5 = c7 = c9 = .. = 0
c0 c2 n = (1) 2 4 6LL 2n (2 + 2v)(4 + 2v)(6 + 2v)LL(2n + 2v)
n

when r = v

Diff_Eq_8_2012

when r = v

## 6.3.1.2 Gamma function: a generalization of n!

( x ) = t x1e t dt
0

60

(1) = 0! = 1

## when n is a positive integer

(2) ( x + 1) = x ( x )
( 2 + v ) = (1 + v) (1 + v ) ( 3 + v ) = (2 + v) ( 2 + v )

Diff_Eq_8_2012

## Solving for Bessel function

( 1) n c0 c2 n = 2 n 2 n !(1 + v)(2 + v)(3 + v)LL (n + v)

61

when r = v

Set

c0 =

(1) n c2 n = 2 n+v 2 n !(1 + v)(2 + v)(3 + v)LL( n + v)(1 + v) (1) n = 2 n+v 2 n !(2 + v)(3 + v)LL (n + v)(2 + v) (1) n = 2 n+v 2 n !(3 + v)LL(n + v)(3 + v) M (1) n = 2 n+v 2 n !(n + v + 1)
Diff_Eq_8_2012

1 2v (1 + v)

r = v

set c0 =

(1) n c2 n = 2 nv 2 n !(n v + 1)
n+ r c x n n =0

1 2 v (1 v)

62

## Two independent solutions of the Bessels equation

When r = v When r = v

(1) n x Jv ( x) = n! (1 + v + n ) 2 n =0

()

2 n+v

(1) n x J v ( x ) = n ! (1 v + n ) 2 n =0

()

2 n v

## Bessel functions of the first kind of order v and v

Diff_Eq_8_2012

We define Jv(x) by

## Bessels Functions of the First Kind

(1) x J v ( x) = n =0 n!(1 + v + n) 2
n 2 n+v

and

(1) x J v ( x ) = n =0 n!(1 v + n) 2
n

2 n v

Diff_Eq_8_2012

## Hence for any value of v, the general solution of (1) is

y = c1 J v ( x ) + c2Yv ( x )
Yv(x) is called the Bessel function of the second kind of order v. shows Y0(x) and Y1(x).
Bessels equation of order v Solution: c1 J v ( x ) + c2Yv ( x )
2 n+v

x 2 y + xy + ( x 2 v 2 ) y = 0 (1) n x Jv ( x) = n! (1 + v + n ) 2 n =0

()

## : 1st kind Bessel function : 2nd kind Bessel function

cos v J v ( x ) J v ( x ) Yv ( x ) = sin v

Diff_Eq_8_2012

6.3.1.4 Bessel function of the 1st kind (order m) (1) J0(0) = 1, Jm(0) = 0 for m 0

Diff_Eq_8_2012

Properties
(1) J ( x ) = ( 1) m J ( x) m m (2) (3)

J m ( x) = (1) J m ( x)
m

0 , m > 0 J m ( 0) = 1 , m = 0

## (4) xJ ( x) = J ( x) xJ ( x). +1 (5) (6)

d x v J ( x) = x v J ( x) v v +1 dx d x v J ( x) = x v J ( x) v 1 dx v

Diff_Eq_8_2012

x0

Diff_Eq_8_2012

## Modified Bessels equation x 2 y + xy + ( x 2 v 2 ) y = 0

2 2 2 2 (A) x y + xy + ( x v ) y = 0

## c1Jv(x) + c2Yv(x) c1Jv( x) + c2Yv( x)

Proof: Set t = x
dy dt dy dy = = dx dx dt dt
2 d 2 y dt d dy dy d y 2 d = Similarly, dx = dt dt = 2 dx dt dx dt 2 2 2 2 dy 2 2 2 2 2 d y 2 t 2 t t x y + xy + ( x v ) y = 2 ( v )y + + 2 2 dt dt 2 dy 2 d y 2 2 Bessel equation t t v ( )y = 0 =t + + 2 dt dt

Diff_Eq_8_2012

## y = c1Jv(t) + c2Yv(t) = c1Jv( x) + c2Yv( x)

(B) modified Bessel equation of order v x 2 y + xy ( x 2 + v 2 ) y = 0 c1Iv( x) + c2Kv(x) 2 2 2 2 x y + xy + (i x v ) y = 0 modified Bessel function of the first v I v ( x ) = i J v ( ix ) kind of order v
y = c1 J v ( ix ) + c 2 J ( ix ), where u m , m = 0,1, 2, L .

## y = c1 J v ( ix ) + c 2Yv ( ix ), where u = m , m = 0,1, 2, L . We modify it to y = A1 J m ( x ) + A2 K m ( x ), where K v ( x ) =

I ( x ) I v ( x ) , K m ( x ) = lim K v ( x ). 2 sin um

Diff_Eq_8_2012

## modified Bessel function of the second kind of order v

Example
Consider the DE
x 2 y"+ xy'+( x 2 1/4) y = 0

## We find v = , and the general solution on (0, ) is

y = c1 J1/2 ( x ) + c2 J 1/2 ( x )

Diff_Eq_8_2012

J
1 2

## (x) = ? 1 = , w e get J 2 (x) =

W ith

1 2

n = 0

x 1 n ! (1 + n + ) 2 2
n

( 1)

2 n +

1 2

B y (1 + ) = ( ) a n d n = 0 : (1 +

1 ) = 2

, w e fin d

1 1 ) = 2 2 3 3 1 3! n = 1 : (1 + ) = = 2 2 2 23 M 1 (2 n - 1) ! ) = . n = n : (1 + n + 2 2 2 n +1 n ! ( 1) n So, J 1 (x) = (2 n - 1) ! n = 0 2 n ! 2 2 n +1 n ! 1 1 F r o m s in x = x x3 + x5 3! 5 !

x 2 L =

2 n +

1 2

n = 0

( 1)n x (2 n + 1) !
2 n +1

2 n +1

n = 0

( 1)n x (2 n + 1) !

so w e get J

1 Diff_Eq_8_2012 2

(x) =

s in x .

## Spherical Bessel Functions

Jv(x)

v = 1 , 3 , 5 , LL 2 2 2 2 sin x x 2 cos x x

## spherical Bessel functions

J1/ 2 ( x) = J 1/ 2 ( x) =

Diff_Eq_8_2012

## 6.3.2 Legendres Equation

6.3.2.1 Legendres Equation (1 x 2 ) y 2 xy + n(n + 1) y = 0

y ( x ) = ck x k
k =0

n(n + 1) 2 (n 2)n(n + 1)(n + 3) 4 y1 ( x ) = c0 1 x + x 2! 4! (n 4)(n 2)n(n + 1)(n + 3)(n + 5) 6 x + LL 6! (n 1)(n + 2) 3 (n 3)(n 1)(n + 2)(n + 4) 5 y2 ( x ) = c0 x x + x 3! 5! (n 5)(n 3)(n 1)(n + 2)(n + 4)(n + 6) 7 x + LL 7! Diff_Eq_8_2012